Transcriptomic analysis of early stages of ‘Candidatus Liberibacter asiaticus’ infection in susceptible and resistant species after inoculation by Diaphorina citri feeding on young shoots - Alves, Mônica N.; Cifuentes-Arenas, Juan; Niñoles, Regina; Raiol-Junior, Laudecir Lemos; Carvalho, Everton; Quirós-Rodriguez, Isabel; Ferro, Jesus A.; Licciardello, Concetta; Alquezar, Berta; Carmona, Lourdes; Forment, Javier; Bombarely, Aureliano; et al. (Frontiers in Plant Science, 2025)
Huanglongbing (HLB) is a devastating disease of citrus plants caused by the non-culturable phloem-inhabiting bacterium Candidatus Liberibacter ssp., being Ca. Liberibacter asiaticus (CLas) the most aggressive species. CLas is vectored by the psyllid Diaphorina citri and introduced into sieve cells, establishing a successful infection in all Citrus species. Partial or complete resistance has been documented in the distant relatives Murraya paniculata and Bergera koenigii, respectively, providing excellent systems to investigate the molecular basis of HLB-resistance. It has been shown previously that the first weeks after bacterial release into the phloem are critical for the establishment of the bacterium. In this study, a thorough transcriptomic analysis of young flushes exposed to CLas-positive and negative psyllids has been performed in Citrus × sinensis, as well as in the aforementioned resistant species, along the first eight weeks after exposure. Our results indicate that the resistant species do not deploy a classical immunity response upon CLas recognition. Instead, transcriptome changes are scarce and only a few genes are differentially expressed when flushes exposed to CLas-positive and negative psyllid are compared. Functional analysis suggests that primary metabolism and other basic cellular functions could be rewired in the resistant species to limit infection. Transcriptomes of young flushes of the three species are very different, supporting the existence of distinct biochemical niches for the bacterium. These findings suggest that both intrinsic metabolic inadequacies to CLas survival, as well as inducible reprogramming of physiological functions upon CLas recognition, could orchestrate together restriction of bacterial multiplication in these resistant hosts.